2021
DOI: 10.31235/osf.io/xmgfu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial/Ethnic Variation in Residential Fathers’ Time in Childcare and Co-presence with Children

Abstract: Past research on racial/ethnic minority fathers’ involvement in children’s lives tends to focus on subgroups of fathers and narrow definitions of involvement, making knowledge of racial/ethnic variation in fathering obscure. Using ordinary-least-squared regression models with the 2003-2019 American Time Use Survey (N = 30,622), we compare White, Black, Latino, and Asian residential fathers’ time spent in four childcare activities and 10 additional daily activities when fathers are co-present with children, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Much of the prior research on contact with family members between Latinos/as and other groups is based on small, geographically limited samples, does not often focus on Latino/a adolescents, and presents mixed findings regarding whether time with family differs between Latinos/as and non‐Latinos/as (Milkie et al, 2004; Nomaguchi et al, 2021; Sarkisian et al, 2006). For studies that specifically focused on adolescents, one study found no differences between Latino/a and White adolescents in levels of current assistance to family, an index that included spending time with nuclear and extended family, eating meals with family, and providing childcare for family members (Fuligni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the prior research on contact with family members between Latinos/as and other groups is based on small, geographically limited samples, does not often focus on Latino/a adolescents, and presents mixed findings regarding whether time with family differs between Latinos/as and non‐Latinos/as (Milkie et al, 2004; Nomaguchi et al, 2021; Sarkisian et al, 2006). For studies that specifically focused on adolescents, one study found no differences between Latino/a and White adolescents in levels of current assistance to family, an index that included spending time with nuclear and extended family, eating meals with family, and providing childcare for family members (Fuligni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In past research using time diaries, this parent-child time is often overlooked because it is categorized as personal care or leisure time of the parent—instead of as care. This socially connected care could be especially vital to mothers and children in Black and Latino communities, where mothers may prioritize care centered in communities and broader networks (Dow, 2016a) and may also value “care” from a more social and integrated lens (Dow, 2016b; Nomaguchi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Socially connected care involves time where mothers introduce and embed children into larger social communities, when interacting or present with children. This type of care may be particularly important for racialized parents, who may define care in a more social way that underscores child development and value-sharing during time together outside of direct "intensive" childcare (Christopher, 2012;Dow, 2016aDow, , 2016bNomaguchi et al, 2022). We point to three potential socially connected care activities in time diaries: time in mothers' own social and community time where children are included, time in religious activities that include children, and time in meals together.…”
Section: Mothers' Time In the Socially Connected Care Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Other explanations for why we did not observe lower levels of happiness among Black mothers compared with Black nonmothers include that Black mothers often experience high levels of community support-in contrast to mothers in White communities, which embrace a more individualist approach to family life (Collins 2002;Dow 2019)-which may promote greater subjective well-being. Black mothers also spend more time in the company of their children (Nomaguchi et al 2022) than White mothers, which has been associated with greater happiness among parents (Negraia and Augustine 2020). More broadly, these findings also indicate that parental status does not play a role in Black-White differences in women's happiness.…”
Section: Discussionmentioning
confidence: 99%